An engineered factor Va prevents bleeding induced by anticoagulant wt activated protein C. - Annette von Drygalski; Vikas Bhat; Andrew J Gale; Laurent Burnier; Thomas J Cramer; John H Griffin; Laurent O Mosnier (PLoS ONE, 2014)
An increased risk of bleeding is observed in patients receiving activated protein C (APC), which may be a limiting factor for the application of novel APC therapies. Since APC's therapeutic effects often require its cytoprotective activities on cells but not APC's anticoagulant activities, an agent that specifically antagonizes APC's anticoagulant effects but not its cytoprotective effects could provide an effective means to control concerns for risk of bleeding. We hypothesized that superFVa, an engineered activated FVa-variant that restores hemostasis in hemophilia could reduce APC-induced bleeding.SuperFVa was engineered with mutations of the APC cleavage sites (Arg506/306/679Gln) and a disulfide bond (Cys609-Cys1691) between the A2 and A3 domains, which augment its biological activity and cause high resistance to APC. SuperFVa normalized APC-prolonged clotting times and restored APC-suppressed thrombin generation in human and murine plasma at concentrations where wild-type (wt) FVa did not show effects. Following intravenous injection of APC into BALB/c mice, addition to whole blood ex vivo of superFVa but not wt-FVa significantly normalized whole blood clotting. Blood loss following tail clip or liver laceration was significantly reduced when superFVa was administered intravenously to BALB/c mice prior to intravenous APC-treatment. Furthermore, superFVa abolished mortality (∼50%) associated with excessive bleeding following liver laceration in mice treated with APC.Our results provide proof of concept that superFVa is effective in preventing APC-induced bleeding and may provide therapeutic benefits as a prohemostatic agent in various situations where bleeding is a serious risk.